2010
DOI: 10.1097/olq.0b013e3181bcd3e7
|View full text |Cite
|
Sign up to set email alerts
|

Concurrency, Sex Partner Risk, and High-Risk Human Papillomavirus Infection Among African American, Asian, and Hispanic Women

Abstract: This study demonstrates that concurrency is associated with HR-HPV and that there may be differences by race/ethnicity in the individual or partnership characteristics of those who report concurrency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Some studies have reported a close association between multiple infections and the increase in the severity of the lesion 10,19 . However, in agreement with other studies, most of the multiple infections in our work were detected in LSIL (57.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a close association between multiple infections and the increase in the severity of the lesion 10,19 . However, in agreement with other studies, most of the multiple infections in our work were detected in LSIL (57.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite representing 15% of the total U.S. population, Latinos account for 17% of newly diagnosed Human Immunodeficiency Virus (HIV) infections and compared to white individuals, Latinos have over twice the rate of gonorrhea and syphilis infection, and nearly three times the rate of chlamydia infection [5][6][7][8] Human Papillomavirus (HPV) awareness in female Latina immigrants has been documented at 47%, which differs from prior HPV awareness study results in other populations (58-75%) [9,10]. Latinas are 1.7 times more likely than other racial/ ethnic minorities to develop high-risk HPV infection, and hence have higher rates of cervical cancer compared with African American and white women (11.6 per 100,000 persons, compared to 9.9 and 7.7, respectively) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 58%
“…One empirical study in the US reported a positive association between Human Papilloma Virus (HPV) prevalence and concurrency for Hispanic women, but a negative association for African Americans, even after controlling for other risk factors [22]. The authors concluded that concurrency is associated with high-risk HPV acquisition and that there may be differences by race/ethnicity in the individual or partnership characteristics of those who report concurrency [22].…”
Section: Additional Neglected Issuesmentioning
confidence: 93%
“…The authors concluded that concurrency is associated with high-risk HPV acquisition and that there may be differences by race/ethnicity in the individual or partnership characteristics of those who report concurrency [22]. Again, the natural history of HPV such as the type-specific immunity following infection, re-activation or re-infection may help to explain why concurrency is associated with the acquisition of HPV (rather than transmission) and why the association is in opposite directions for Hispanic women (concurrency increases HPV) and African American women (concurrency decreases HPV).…”
Section: Additional Neglected Issuesmentioning
confidence: 95%
See 1 more Smart Citation